ANALYSIS OF Pb, Cu, and Zn CONCENTRATIONS IN SNAIL (Cerithidea montagnei)FROM SELAT AIR HITAM WATERS OF KEPULAUAN MERANTI REGENCY, RIAU PROVINCE - Darma Bagus Saputra; Bintal Amin; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in March 2018 with the aim to determine the concentration of Pb, Cu and Zn, and their relation to the size of snail (Cerithidea montagnei) and to determine the safe limits of snail consumption, and to estimate the level of metal pollution in the waters of Air Hitam Strait. Sampling locations were determined by using purposive sampling and was conducted in areas with relatively different anthropogenic activities. Heavy metal concentration analysis was performed at the Marine Chemistry Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The results showed that the metal content of Pb at station 1 was 1,128 μg/g and in station 2 that was 1,000 μg/g, Cu at station 1 was 45,480 μg/g and in station 2 was 69,756 μg/g while Zn at station 1 was 115,556 μg/g and at station 2 is 152,836 μg/g. A simple linear regression analysis between the size and the metal concentration of Pb in the snail showed a strong relationship, while Cu and Zn concentration showed a moderate relationship. The safe limit of snail consumption in the waters of Air Hitam Strait for Pb metal is 6.6789 kg/week, Cu is 17.0086 kg/week and Zn is 14.6055 kg/week. The MPI value forAir Hitam Strait is 20.19, which illustrates that the waters of the Strait is in the state of relatively polluted. Keywords: Pollution, Heavy Metal, KepulauanMeranti Regency